A comparative study of serum calcium, magnesium and its ratio in women of menopausal and reproductive age group - Sukumaran, Seena (International Journal of Research in Medical Sciences, 2017)
Background: The menstrual cycle is the result of complex interacting processes within the hypothalamus, the hypophysis, the ovaries and the uterus. Patterns of change in plasma concentrations of various minerals have been the subject of several research endeavours. Therefore, the present study has been conducted to study and compare the serum calcium, magnesium and its ratio in menopausal and reproductive age group. Methods: The study was performed in two groups of subjects with a control group of 30 healthy women of reproductive age group and a postmenopausal group of 30 women with varying durations of menopause (less than and more than 10 years after menopause). Three blood samples were obtained from the control group –one each in early follicular phase, ovulatory phase and during luteal phase for estimation of calcium and magnesium. One sample was taken from the menopausal age group for the estimation of calcium and magnesium using commercially available kit. The values are expressed as mean ± S.D. The comparison between the different phases of menstrual cycle in reproductive age group with menopausal women was performed using student t-test. P value less than 0.05 was considered significant. Result: The serum Ca2+, Mg2+ and Calcium/ Magnesium ratiowas found to be statistically insignificant (p=1.00), during different phases of menstrual cycle in normal cycling women is statistically insignificant. Discussion: The cyclical changes of serum Ca2+ and Serum Mg2+ levels in women of reproductive age may be due to the cyclical changes in the level of sex hormones during different phases of menstrual cycle.